Bioactive Components of Soybean as a Source of Medicinal Products - Levashova, Olga; Gaponenko, Valentina; Syrovaya, Anna; Gontova, Tetiana (My University, 2017)
This article presents the results of qualitative and quantitative composition of biologically active substances of green mass 6 recognized varieties of soybean, soybean seeds, soybean meal after oil extraction and biologically active complex of soy. The presence of 21 amino acids, 7 flavones, 6 isoflavones, 2 coumarin, 4 phenolcarbonic acid, tannins, vitamins (E, K, P, B), polysaccharides was determined. The resource-saving technology of oil production, biologically active complex and protein were developed.
Keywords: soybean; biologically active substances; green mass; meal; qualitative composition; quantitative; biologically active complex